Classification changes in para swimming and their impact on the Czech Para Swimming Team - Vít Šašek; Klára Daďová; David Půlpán (Karolinum Press, 2022)
This aim of this article is to describe up-to-date polices and main classification issues in Paralympic sport with focus on Paralympic swimming. Using narrative review, it determines the influence of recent classification changes by reviewing available research data on how the classification system works and what direction it has taken after January 2018 when the new Classification Manual for swimming was published. It analyzes those changes in Czech Para Swimming Team during 4-year-period leading up to Tokyo Paralympic Games 2020 including 3 major swimming competetions and Paralympic Games itself. The results show the changes directly influenced the performance of Czech para swimmers in mentioned major competetions in a positive way. Czech Para Swimming Team added two more medals and gained more spots for both men and women for Tokyo Paralympic Games 2020 effectively extending relatively small Czech Paralympic Team in Tokyo.